2023
DOI: 10.3390/fractalfract7050383
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Rock Damage Intensity Controlled by Mineral Compositions: Insights from Fractal Analyses

Abstract: Since each rock type represents different deformation characteristics, prediction of the damage beforehand is one of the most fundamental problems of industrial activities and rock engineering studies. Previous studies have predicted the stress–strain behaviors preceding rock failure; however, quantitative analyses of the progressive damage in different rocks under stress have not been accurately presented. This study aims to quantify pre-failure rock damage by investigating the stress-induced microscale crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…The larger the grain size, the rougher the rock surface profile. It can be concluded that high fractal dimension values will be owned by materials with coarse grain size, but it does not apply to materials with uniform grain shape [33]. The fractal dimension provides a distinct quantitative approach to describe surface roughness that can be characterized qualitatively.…”
Section: Fractal Analysismentioning
confidence: 99%
“…The larger the grain size, the rougher the rock surface profile. It can be concluded that high fractal dimension values will be owned by materials with coarse grain size, but it does not apply to materials with uniform grain shape [33]. The fractal dimension provides a distinct quantitative approach to describe surface roughness that can be characterized qualitatively.…”
Section: Fractal Analysismentioning
confidence: 99%
“…Fractal and multifractal methods have been shown to be effective in delineating diverse complex geological patterns, as mentioned above; however, most studies have focused on recognizable macroscopic geometries, such as structures, geophysical and geochemical anomalies, and ore-related evidence, while only a few contributions have employed fractal analyses for mineral pattern characterization at the microscopic scale. Notably, mineralogical research has long been considered fundamental for ore-forming systems, while fractal-derived indices are quite suitable for characterizing the main targets of mineralogical studies, including but not limited to morphological descriptions [30], micro-structures [31], compositional variance [32,33], special textures [29] and mineral staging [13]. The microscopic information extracted from these fractal indices and their underlying scaling properties of mineral patterns can be utilized to trace the footprints of pattern-forming geological processes, which are crucial to understanding mineralization and/or diagenetic systems [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Heng et al [7] introduced the failure form of coal and gangue composite structures and explored the precursor signal characteristics of failure and instability of coal and gangue composite structures under an unloading path. Guo Weiyao et al [8][9][10] simulated uniaxial and biaxial compression tests of a coal-rock composite specimen with different coal-rock strength ratios and height-diameter ratios by using PFC2D 5.0 particle flow software. Wu Genshui et al [11] carried out research on the influence of coal-rock mass structure and fracture on the stability of a coal-bolt composite system and carried out experimental analysis and theoretical verification on the RCB composite system at different angles.…”
Section: Introductionmentioning
confidence: 99%